Engineered exosomes: a potential therapeutic strategy for septic cardiomyopathy - Mao, Lixia; Liu, Songtao; Chen, Yongxia; Huang, Huiyi; Ding, Fenghua; Deng, Liehua (Frontiers in Cardiovascular Medicine, 2024)
Septic cardiomyopathy, a life-threatening complication of sepsis, can cause acute heart failure and carry a high mortality risk. Current treatments have limitations. Fortunately, engineered exosomes, created through bioengineering technology, may represent a potential new treatment method. These exosomes can both diagnose and treat septic cardiomyopathy, playing a crucial role in its development and progression. This article examines the strategies for using engineered exosomes to protect cardiac function and treat septic cardiomyopathy. It covers three innovative aspects: exosome surface modification technology, the use of exosomes as a multifunctional drug delivery platform, and plant exosome-like nanoparticle carriers. The article highlights the ability of exosomes to deliver small molecules, proteins, and drugs, summarizing several RNA molecules, proteins, and drugs beneficial for treating septic cardiomyopathy. Although engineered exosomes are a promising biotherapeutic carrier, they face challenges in clinical application, such as understanding the interaction mechanism with host cells, distribution within the body, metabolism, and long-term safety. Further research is essential, but engineered exosomes hold promise as an effective treatment for septic cardiomyopathy. remains unclear, highlighting the need for more effective and safer therapeutic approaches for septic cardiomyopathy.Extracellular vesicles (EVs), which are nanoscale lipid bilayer membrane structures secreted by cells (Debbi, Guo et al. 2022), can be divided into two main categories based on their generation mechanisms: endosome-origin exosomes and plasma membrane-derived ectosomes (van Niel, D'Angelo et al. 2018, Dixson, Dawson et al. 2023). Exosomes, as naturally occurring extracellular vesicles with diameters ranging from 30 to 200 nm, have garnered considerable interest in recent years. Found in various biological fluids, almost all eukaryotes or prokaryotes can release, these vesicles that carry a range of cellular components, including lipids, proteins,